Influence of native catfish mucus on Flavobacterium columnare growth and proteolytic activity. Issue 9 (11th June 2018) - Shoemaker, Craig A.; LaFrentz, Benjamin R.; Peatman, Eric; Beck, Benjamin H.
Abstract: Flavobacterium columnare causes columnaris disease of farmed and wild freshwater fish. Skin mucus is an important factor in early stages of columnaris pathogenesis, albeit little studied. Our objectives were to (a) characterize the terminal glycosylation pattern (TGP) of catfish mucus, (b) determine the growth of F. columnare in formulated water (FW)‐containing channel catfish ( Ictalurus punctatus ) or hybrid catfish ( Ictalurus punctatus X Ictalurus furcatus ) mucus and (c) examine extracellular protease activity of two F. columnare isolates differing in virulence. The TGP of catfish mucus by lectin binding was as follows: alpha‐D‐mannose/alpha‐D‐glucose >N‐acetyl‐beta‐D‐glucosamine >N‐acetyl‐beta‐D‐glucosamine/N‐acetylneuraminic acid >N‐acetyl‐D‐galactosamine >alpha‐D‐galactose/N‐acetyl‐alpha‐D‐galactosamine >beta‐D‐galactose = alpha‐L‐fucose. Virulence studies demonstrated isolate AL‐02‐36 was highly virulent in channel catfish fry (0.1 g) with cumulative mortality of 90%‐100% versus 60% for isolate ALG‐00‐530 at equivalent doses (~3 × 10 6  CFU/ml); a similar result was observed in larger (0.7 g) catfish. In multiple experiments, F. columnare replicated (2‐3 logs) and survived (28 days) in formulated water‐containing catfish mucus. Highly virulent isolate AL‐02‐36 possessed at least 2.5‐ to fivefold higher protease activity following growth in mucus than the less virulent ALG‐00‐530. Flavobacterium columnare utilized catfish mucus as a nutrient source and mucus presence modulated extracellular protease production.